Urban value proposition of industrial built heritage - Kees Geevers (A+BE: Architecture and the Built Environment)
This dissertation is the reflection of the research study into urban planning structures of historic industrial complexes. The study’s aim has been to promote recognition and acknowledgement of these structures as the carriers of cultural-historical values in spatial transformation.